Dialectical behavior therapy : a contemporary guide for practitioners - Pederson, Lane (Chichester, West Sussex ; Hoboken : Wiley Blackwell, 2015)
A definitive new text for understanding and applying Dialectical Behavior Therapy (DBT).-Offers evidence-based yet flexible approaches to integrating DBT into practice -Goes beyond adherence to standard DBT and diagnosis-based treatment of individuals -Emphasizes positivity and the importance of the client's own voice in assessing change -Discusses methods of monitoring outcomes in practice and making them clinically relevant -Lane Pederson is a leader in the drive to integrate DBT with other therapeutic approaches.
13 Self-Monitoring with the Diary CardDiary card; 14 Validation; Levels of Validation; Validation versus Normalization; 15 Commitment Strategies; Note; 16 Educating, Socializing, and Orienting; Example 1; Example 2; 17 Communication Styles; Reciprocal Communication; Irreverent Communication; Notes; 18 Mindfulness; Note; 19 Skills Training; 20 Changing Behaviors; Behavioral Contingencies; Behaviorism and the Therapist; The Most Effective Methods of Changing Behaviors; Notes; 21 Behavioral Analysis; Behavioral Analysis Example; Note; 22 Dialectical Strategies; Note; 23 Cognitive Interventions.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Cognitive therapy; Cognitive Therapy -- methods; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Cognitive therapy; Dialectical behavior therapy; MEDICAL -- Psychiatry -- General; PSYCHOLOGY -- Clinical Psychology; Electronic books